Augmenting English public speaking skill through peer evaluation: a case study in Toastmaster International Club - Lailatul Rifah; Fardini Sabilah (Universitas Islam Negeri Palangka Raya, Indonesia, 2022)
Having peers to give public speaking feedback is always feasible to measure the learners